1958
DOI: 10.1103/physrev.111.297
|View full text |Cite
|
Sign up to set email alerts
|

Scattering of 220-Mev Polarized Protons by Complex Nuclei

Abstract: Extending earlier measurements, we have studied yields and asymmetries in the scattering of a highly polarized proton beam by Be 9 , C 12 , Al 27 , and Ca 40 . In the work on Be 9 and Al 27 , the beam was monochromatized through the use of a regenerative deflector; its mean energy on striking the targets was 219.6 Mev, and its standard deviation in energy (including the effect of short time fluctuations) was less than 1.1 Mev. With this technique, together with a refined procedure for the analysis of the distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1959
1959
2000
2000

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…3, and compared with the values given by Hafner. 3 We have shown that our ^p polarization results are not affected by instrumental biases. However, some systematic error, due principally to the arbitrariness when interpolating in the table of the analyzing power of carbon, could still affect our results.…”
Section: Left Position Polarizationmentioning
confidence: 56%
See 1 more Smart Citation
“…3, and compared with the values given by Hafner. 3 We have shown that our ^p polarization results are not affected by instrumental biases. However, some systematic error, due principally to the arbitrariness when interpolating in the table of the analyzing power of carbon, could still affect our results.…”
Section: Left Position Polarizationmentioning
confidence: 56%
“…3 The test was made with incident protons of this energy using an experimental setup similar to that for the pion-proton measurement. The hydrogen target was replaced by a carbon plate 1.7 cm thick.…”
mentioning
confidence: 99%
“…Pi was calculated from data of Dickson and Salter, 15 Tyren et a/., 16 and Hafner. 17 The values of P 2 =e 2 /Pi quoted in Table VIII are the averaged values given in Foote. 2…”
Section: Calibrationmentioning
confidence: 99%